Highly stretchable porous regenerated silk fibroin film for enhanced wound healing. Issue 7 (19th January 2023) - Sun, Fengchao; Xiao, Dongdong; Su, Hui; Chen, Zhiliang; Wang, Bijia; Feng, Xueling; Mao, Zhiping; Sui, Xiaofeng
Abstract : Silk fibroin (SF) has caught interest in tissue engineering owing to their biocompatibility and biodegradability. Abstract : Silk fibroin (SF) has received interest in tissue engineering owing to its biocompatibility, biodegradability, and favorable mechanical properties. However, the complex preparation, brittleness, and lack of pores in the structure of the silk fibroin film limit its application. Herein, we show that facile dissolution of SF in aqueous phosphoric acid followed by regeneration in aqueous ammonium sulfate ((NH4 )2 SO4 ) could afford highly stretchable films with nano-pores formed in the nonsolvent-induced phase separation process. The named phase separation, which determines the morphology and mechanical properties of the regeneration silk fibroin (RSF) films, is highly dependent on the (NH4 )2 SO4 concentration as well as the initial concentration of the SF solution. Therefore, the RSF films exhibit a tunable pore size ranging from 230 to 510 nm and excellent stretchability with tensile strain up to 143 ± 16%. Most interestingly, the RSF films were shown to support the proliferation of human skin fibroblasts in vitro as well as speed up full-thickness skin wound healing in a rat model. This work establishes an easy and feasible method to access porous RSF membranes that can be used for wound dressing in clinical settings.